2005
DOI: 10.1007/s00291-005-0001-8
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the distributions of cash flows and discount rates in multiperiod valuation problems

Abstract: n capital budgeting problems future cash flows are discounted using the expected one-period returns of the investment. In this paper we relate this approach to the assumption that markets are free of arbitrage. Our goal is to uncover implicit assumptions on the set of cash flow distributions that are suitable for the capital budgeting method. Our results are twofold. First we obtain that for deterministic cost of capital the set of admissible cash flow distributions is large in the sense that no particular str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…17 See for an equivalent statement, e.g., Laitenberger and Löffler (2006) and Kruschwitz and Löffler (2006). 18 For the mathematical proof, we refer to Appendix 10.…”
Section: Unlevering Betamentioning
confidence: 99%
See 1 more Smart Citation
“…17 See for an equivalent statement, e.g., Laitenberger and Löffler (2006) and Kruschwitz and Löffler (2006). 18 For the mathematical proof, we refer to Appendix 10.…”
Section: Unlevering Betamentioning
confidence: 99%
“…8 By assuming auto-regressive free cash flows as in Eq. (1), only one additional condition, e.g., the dividend ratios are deterministic, is necessary to prove that cost of capital is deterministic (see Laitenberger and Löffler 2006). Deterministic cost of capital is required to determine the value of a firm contingent on the available information at t.…”
Section: The Model 21 Basicsmentioning
confidence: 99%
“…In Barberis et al (1998) a violation of auto-regression was considered, although in a very different context. Our specific formulation of weak auto-regressive cash flows was first systematically examined in Laitenberger and Löffler (2006). That is also where theorems on the relation between cost of capital and conditional expected returns are found.…”
Section: Further Literaturementioning
confidence: 99%
“…The topic of the prognosis of future cash flows is unfortunately very often left out, Welch (2014, chapter 20) is a notable exception. Rapp (2006) and Laitenberger (2006) discuss the question whether a suitable definition of cost of capital can be found that does not need the restriction of nonrandom returns.…”
Section: Further Literaturementioning
confidence: 99%